1996
DOI: 10.1046/j.1365-2265.1996.701521.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for secondary hyperparathyroidism in a nursing home population

Abstract: Vitamin D deficiency is a common risk factor for secondary hyperparathyroidism in nursing home residents despite a climate in which vitamin D nutrition is thought to be ample. However, the daily frusemide dose is a more important predictor of PTH in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 32 publications
4
46
1
1
Order By: Relevance
“…This observation suggested that excessive urinary calcium losses in CKD patients, who are prone to tenuous calcium balance because of relative calcitriol deficiency, may promote intermittent reductions in serum calcium with resulting spikes in PTH, which eventually manifest clinically as secondary hyperparathyroidism. This hypothesis is supported by studies in the general population and CKD that showed that excessive calciuria driven by loop diuretics was associated with elevated PTH (7)(8)(9)(10)(11).…”
Section: Introductionsupporting
confidence: 67%
“…This observation suggested that excessive urinary calcium losses in CKD patients, who are prone to tenuous calcium balance because of relative calcitriol deficiency, may promote intermittent reductions in serum calcium with resulting spikes in PTH, which eventually manifest clinically as secondary hyperparathyroidism. This hypothesis is supported by studies in the general population and CKD that showed that excessive calciuria driven by loop diuretics was associated with elevated PTH (7)(8)(9)(10)(11).…”
Section: Introductionsupporting
confidence: 67%
“…Following MV supplementation, serum 25(OH)D concentrations increased by a mean of 27 nmol l À1 (77%), and reduced the rate of serum 25(OH)D deficiencies (p50 nmol l À1 ) from 77 to 23%, with no subjects having an insufficient level (p25 nmol l À1 ). In Australia, the number of aged care residents with low 25(OH)D levels is high, with estimates ranging between 22 and 74% (Stein et al, 1996;Flicker et al, 2003;. Only one previous study in community dwelling elderly assessed 25(OH)D concentrations following 8 weeks of MV supplementation, which found an increase in serum 25(OH)D of 30%, reducing the rates of serum 25(OH)D levels o37.5 nmol l À1 from 7 to 0% (McKay et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Before the diagnosis of normocalcemic PHPT can be established, it will be highly important to rule out carefully any other potential causes of high PTH as outlined (9). This includes any chronic disease associated with malabsorption such as cystic fibrosis (13) or celiac disease (14), both conditions often being associated with vitamin D deficiency endocrinopathies such as hypothyroidism (15), renal hypercalciuria (16), chronic renal failure (the definition of which must be more clearly defined in terms of GFR), very low daily calcium intake, use of drugs having an influence on calcium metabolism such as anticonvulsants (17), furosemide (18), lithium (19), or bisphosphonates (20), and vitamin D insufficiency. Concerning this last condition, it is now consensual that serum 25OHD is the correct functional indicator of vitamin D status (21).…”
Section: Discussionmentioning
confidence: 99%